Emergence of deadly viral haemorrhagic fever disease outbreaks in West Africa. Issue 1 (31st December 2023) - Vega-Rodriguez, Widaliz; Ly, Hinh
ABSTRACT: Recent viral hemorrhagic fever (VHF) disease outbreaks caused by Ebola virus (EBOV) and Marburg virus (MARV) in West Africa are unique and alarming. The intents of this editorial are to highlight what is known about these viruses and the disease outbreaks that they cause in the African continent and elsewhere and to raise awareness of a related virus called Lassa virus (LASV) that causes endemic viral hemorrhagic fever infections and frequent outbreaks in West Africa.